Analyzing pedestrian merging flow on a floor–stair interface using an extended lattice gas model. (May 2014) - Huo, Feizhou; Song, Weiguo; Lv, Wei; Liew, K M
The floor–stair interface is a critical component of the escape stairs in high-rise buildings, and the characteristics of the merging flow in the floor–stair interface is also significant for investigating the evacuation of high-rise buildings. In this paper, the original lattice gas model is extended by considering inner-side walking preferences, turning behavior and different desired speeds. Then the merging flow in the floor–stair interface is simulated with the extended model. The fundamental diagram of the simulation results has the same tendency as the empirical data and it is found that the merging at the floor–stair interface could retard the motion of pedestrians on the incoming stairs and reduce the motion speed in the case when the corridors are adjacent to the incoming stairs. The effect of two kinds of typical structures of the floor–stair interface on pedestrian merging behavior is investigated. The results show that the evacuation process will be improved when the corridor is connected to the landing opposite to the incoming stairs. The results given in this paper may be helpful in understanding the characteristics of pedestrian merging flow in floor–stair interfaces and in designing building structures.